ANALYSIS OF EXTERNAL FACTORS AFFECTING STUDENTS' ENGLISH SPEAKING ABILITY - SINTA NOVIA; LILI ANTIKA; RIA RESTU OCTAVIANI; CANTIKA CINTAMI AYU (JETA (Journal of English Teaching and Applied Linguistic), 2025)
This study aims to analyze the external factors that influence students' English speaking ability at SMP Muhammadiyah Dua Bandar Lampung. The external factors studied include the influence of classroom environment, media, and parental support in learning English. The research method used was a qualitative approach with observation technique and documentation study. Data were collected through direct observation in the classroom and analysis of learning materials and parental support in students' learning activities. The results show that a supportive classroom environment, such as interaction with peers who are fluent in English, as well as the use of relevant media, such as movies and English learning apps, have an important role in improving students' speaking skills. In addition, parental support, such as providing opportunities to attend language courses or practice outside of school, also positively influences students' speaking ability. Based on these findings, it is recommended that schools and parents work together to create an environment that supports the development of students' English speaking ability.